Homologous Cloning of Potassium Channel Genes From the Superior Apple Rootstock Line 12-2, Which is Tolerant to Apple Replant Disease - Mao, Yunfei; Yin, Yijun; Cui, Xueli; Wang, Haiyan; Su, XiaFei; Qin, Xin; Liu, Yangbo; Hu, Yanli; Shen, Xiang (Frontiers in Genetics, 2022)
Potassium channels are important ion channels that are responsible for the absorption of potassium in the plant nutrient uptake system. In this study, we used homologous molecular cloning to obtain 8 K+ channel genes from the superior apple rootstock line 12-2 (self-named): MsAKT1-1, MsKAT3-2, MsKAT1-3, MsK2P3-4, MsK2P3-5, MsK2P5-6, MsK2P3-7, and MsK2P3-8. Their lengths varied from 942 bp (MsK2P5-6) to 2625 bp (MsAKT1-1), and the number of encoded amino acids varied from 314 (MsK2P5-6) to 874 (MsAKT1-1). Subcellular localization predictions showed that MsAKT1-1, MsKAT3-2, and MsKAT1-3 were localized on the plasma membrane, and MsK2P3-4, MsK2P3-5, MsK2P5-6, MsK2P3-7, and MsK2P3-8 were localized on the vacuole and plasma membrane. The 8 K+ channel proteins contained α helices, extended strands, β turns, and random coils. MsKAT1-3 had four transmembrane structures, MsKAT3-2 had six, and the other six K+ channel genes had five. Protein structure domain analysis showed that MsAKT1-1 contained nine protein domains, followed by MsKAT3-2 with four, MsKAT1-3 with three, and the other five two-pore domain K+ channel proteins with two. Semi-quantitative RT-PCR detection of the K+ channel genes showed that their expression levels were high in roots. qRT‑PCR analysis showed that the relative expression levels of the 8 genes changed after exposure to ARD stress. The above results provide a theoretical basis for further research on the functions of potassium channel genes in 12-2 and a scientific basis for the breeding of ARD-resistant rootstock.